2022
DOI: 10.3390/stats5040060
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Generalization of Zero-Truncated Binomial Distribution by Lagrangian Approach with Applications for the COVID-19 Pandemic

Abstract: The importance of Lagrangian distributions and their applicability in real-world events have been highlighted in several studies. In light of this, we create a new zero-truncated Lagrangian distribution. It is presented as a generalization of the zero-truncated binomial distribution (ZTBD) and hence named the Lagrangian zero-truncated binomial distribution (LZTBD). The moments, probability generating function, factorial moments, as well as skewness and kurtosis measures of the LZTBD are discussed. We also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The values λ, μ, and ρ obtained by maximizing L n with respect to λ, µ, and ρ, respectively, are the ML estimates (MLEs). Upon differentiating the log-likelihood function given in (18) with respect to the parameters λ, µ, and ρ, respectively, and equating to zero, we obtain the following likelihood equations:…”
Section: Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The values λ, μ, and ρ obtained by maximizing L n with respect to λ, µ, and ρ, respectively, are the ML estimates (MLEs). Upon differentiating the log-likelihood function given in (18) with respect to the parameters λ, µ, and ρ, respectively, and equating to zero, we obtain the following likelihood equations:…”
Section: Estimationmentioning
confidence: 99%
“…Our team was very impressed by the competency of the distributions proposed based on the Lagrangian method, and as a result, we proposed the Lagrangian version of ZTPD through the work published in [17]. Furthermore, the authors in [18] concentrated on the Lagrangian approach's construction of the zero-truncated binomial distribution (ZTBD) and explained how effective it was in comparison to other zero-truncated distributions. The aforementioned relevance once more compelled us to develop solutions to intervention problems using a Lagrangian approach, which we dub the LIPD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors in [18] also used the LD 2 to create the generalized LKD of type two. The competence of the distributions proposed based on the LD 2 profoundly attracted our team, and as a result, we suggested the Lagrangian version of the ZTPD, the zero-truncated binomial distribution, and the IPD (see [26][27][28]). Moreover, the authors in [24] demonstrated that every member of the LD 2 was also a member of the LD 1 .…”
Section: Introductionmentioning
confidence: 99%